wing in wing ? wing and wing ??? (1974)
wing-and-wing For instance, somebody came in with a big shout an' said,"Here she comes! She's coming in the bay wing in wing." Now nobody knew what wing in wing meant, but we of course knew that we had the expression made on board schooners when we made voyages. . But as we'd slack off the main sheet and the fore sheet as well, an' keep them both in that true position, it meant that we were following a true course exactly as the wind, because of the varied we wouldn't go wing in wing, we'd go by the wind, if we went far enough to win'ard. Yes J.D.A. WIDDOWSON AUG 1974 Not used Not used Withdrawn withdrawn but no stamp